AN INTELLIGENT TALENT RECOGNITION OF MALE YOUTH FIELD HOCKEY PLAYERS USING PHYSICAL FITNESS, ANTHRO-ENERGY INTAKE AND PSYCHOLOGICAL VARIABLES - Norzulaika, Alias; Hafizan, Juahir; Mohamad Razali, Abdullah (2018)
The aim of this study was to determine the most significant of physical fitness, anthro-energy intake and psychological variables in identifying the talented male youth field hockey players. 40 male players (age, 14.6 ± 1.2 years) from Terengganu sport academy were evaluated in different tests and measurements. The rotated PCs resulted 4 components were significant in physical fitness, 8 components were significant in anthro-energy intake and 7 components were significant in psychology. HACA classified the players into 3 groups: high, middle and low performance. The precision of classification using standard, forward and backward stepwise mode have yielded 85.00%, 95.00% and 97.50%. Thus, certain components significantly involved in the talent identification of field hockey players. Effective specified trainings should be considered to increase performance among them.